Preparation of TiO2 photoanode on flexible ITO coated PET for dye sensitized solar cell - Shaban, Suraya; Shafie, Suhaidi; Lokman, Muhammad Quisar; Ahmad, Fauzan (2018)
This paper discussed the progress of research on fabrication of flexible dye-sensitized solar cells (DSSCs) using ITO/PET in replacing the conventionally used FTO glass substrates. A major challenge for making DSSCs on plastic substrates is the temperature limitation of the plastic in producing the TiO2 photoanode. Such test using low-temperature fabrication methods for TiO2 films, such as hydrothermal treatment of paste using binder and free-binder paste were applied, the timing for sintering in oven and furnace, also the results after dipped in dye were discussed.